Normal Reorganization Plan for Saving Struggling Economic Projects In Pursuant to the Jordanian Insolvency Law: A Comparative Study - Al-Arnaout , Ibrahim Sabri (Dirasat: Shari’a and Law Sciences, 2020)
The research deals with the text of Article (79) of the Jordanian Insolvency Law No. (21) of 2018 in force, which relates to the subject of the regular reorganization plan to rescue faltering economic projects. The text is based and its scope revolves around the legal means and procedures that faltering economic projects can resort to when declaring their insolvency. By submitting a reorganization plan to the competent court to arrange its economic conditions and continue the activity instead of judicial liquidation and the consequent liquidation of the project. This ensures that workers are kept in their business and creditors’ interest is achieved by repaying their debts and the continuation of cash flows, and other effects that reflect positively on the investment environment and achieve economic and social development. We have pointed out the weakness of the legal mechanisms to rescue faltering economic projects in the Jordanian insolvency law as a result of the absence of an expert insolvency committee in the courts with the task of examining the project and the extent to which it is necessary to undergo restructuring, and the failure to provide for a role for the insolvency judge. The law also lacks simplified procedures for small and medium economic enterprises.